Colourimetric determination of features of an air sampling technique optimal for detection of surfactants - Nur Hazimah Abdul Halim; Norfazrin Mohd. Hanif; Mohamed Rozali Othman; Mohd. Talib Latif (Universiti Kebangsaan Malaysia, 2010)
Surfactants in the atmosphere may act as cloud condensation nuclei, with a potentially negative impact on the global climate. Therefore, accurate determination of surfactants is crucial in order to investigate the possible effects of surfactants on the atmosphere. The aim of this study was to identify the optimum sampling method for measuring the maximum quantity of surfactants present in ambient air. Air samples were collected using a range of air sampling pumps that were made to vary in terms of flow rate, storage period, type of absorbing solution and the characteristics of the impinger tube. Samples obtained were analysed by colourimetry for anionic and cationic surfactants as methylene blue-active substances (MBAS) and disulphine blue-active substances (DBAS), respectively. Absorbance was measured at 650 nm for MBAS and 628 nm for DBAS using UV-visible spectrophotometer. We found that the optimum sampling method consisted of an absorbent solution (deionised water, buffer solution and methylene blue/disulphine blue solution) with the flow rate of 1.0 L/min. The concentration of surfactants in all sampling methods remained constant regardless of the storage period (1 day and 4 days), indicating that surfactants in the absorbing solution are quite stable. Covering the impinger tube was shown to influence the amount of both anionic and cationic surfactants detected.